Les representacions de la poesia escènica de Joan Brossa entre el 1947 i el 1959 - Eduard Planas (Caplletra: Revista Internacional de Filologia, 2015)
The author presents a study of Joan Brossa's Scenic Poetry, both from a reading of the texts and by a follow-up and analysis of their consummation on stage. This is a first approach to the performances of the period comprised between 1947 and 1959, and an advance of basic general conclusions.